Starter Selection for Diesel Engines - Osman Dur; Nedim Sözbir; Şenol Gülgönül (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2023)
Starter selection is a critical decision in diesel engine design. The starter performance curves are generally accepted in the industry, with current on the horizontal axis and power, volts, speed and starter torque on the vertical axis. In this way, it is not possible to compare the starter performance curves with the engine friction force curve. In this study, a method has been developed for the selection of suitable starter for diesel engines. With the developed method, the starter performance curve is converted and the engine friction curve is shown on the same graph. With this method, it can be easily understood whether the starter is suitable for a diesel engine. In addition, possible problems that may be encountered during cold start-up can be foreseen. The developed method uses actual performance measurements given by the starter manufacturer. On the engine side, if there is an existing engine, engine friction test results are used. If the engine is in the design phase, the friction force results obtained by simulation are used.